Miocardiopatía hipertrófica septal, la gran simuladora - Forero, Santiago (2021)
Hypertrophic cardiomyopathy is the more commonly (60 to 70 percent) genetically determined disease of the heart muscle caused by mutations in one of several sarcomere genes that encode components of the heart’s contractile apparatus. It is characterized by disproportionate hypertrophy in the absence of a secondary cause. The clinical presentation is variable, ranging from asymptomatic to heart failure or sudden cardiac death. Hypertrophy and abnormal ventricular configuration can result in dynamic left ventricular outflow obstruction in most cases. The goal of therapeutic interventions is largely to reduce dynamic obstruction, with different therapeutic options encompassing risk stratification for sudden death, genetic screening, lifestyle modifications, and drugs. A case of hypertrophic septal cardiomyopathy, a fairly frequent and under-diagnosed entity, is discussed below.